2020
DOI: 10.1177/1747021820935776
|View full text |Cite
|
Sign up to set email alerts
|

Absolute pitch learning in adults speaking non-tonal languages

Abstract: Absolute pitch (AP) refers to labelling individual pitches in the absence of external reference. A widely endorsed theory regards AP as a privileged ability enjoyed by selected few with rare genetic makeup and musical training starting in early childhood. However, recent evidence showed that even adults can learn AP, and some can attain a performance level comparable to natural AP possessors. These training studies involved native tonal language speakers, whose acquisition of AP might be facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(111 reference statements)
0
6
0
1
Order By: Relevance
“…Instead, the superior AP performance among AP possessors can be supported by their more efficient perceptual analyses of tones. This hypothesis also provides a neural basis for the recent proposal that the acquisition of AP may be critically determined by one's ability to maintain the content of tonal working memory despite incoming tonal interference (Van Hedger et al, 2015;Wong et al, 2020).…”
Section: Perceptual Advantage Of Tone Processing In Apmentioning
confidence: 86%
See 1 more Smart Citation
“…Instead, the superior AP performance among AP possessors can be supported by their more efficient perceptual analyses of tones. This hypothesis also provides a neural basis for the recent proposal that the acquisition of AP may be critically determined by one's ability to maintain the content of tonal working memory despite incoming tonal interference (Van Hedger et al, 2015;Wong et al, 2020).…”
Section: Perceptual Advantage Of Tone Processing In Apmentioning
confidence: 86%
“…The prevalence of AP ranges from 1 in 10,000 in the general population (Takeuchi & Hulse, 1993;Ward, 1999), to 7%-50% in musicians in colleges and conservatories (Deutsch et al, 2006;Miyazaki et al, 2012). Past AP research on its etiology highlighted the importance of genetic factors and early exposure in a sensitive period of development (Bachem, 1940;Baharloo et al, 1998Baharloo et al, , 2000Gregersen et al, 1999;Zatorre, 2003) and tonal language background (Deutsch et al, 2009), though recent studies demonstrated the possibility of adult musicians to acquire pitch naming performance comparable to musicians with AP (Wong et al, 2019(Wong et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Classical thought spoke of harmony as a cosmological ideal, trying to use the term to talk in terms of not just music, but of the movement of stars (Miller, 1986). That classical reasoning drove the question as to why a person having perfect pitch is closer to being a person of intelligence (Wong, Ngan, Cheung, & Wong, 2020) However, Spearman and other later researchers had to abandon the hopes of finding almost a causal variable to intelligence in the phenomenon of perfect pitch. As the debate has raged over the years, beyond the low mathematical correlation to g, perfect pitch was found to have a higher incidence among different linguistic and ethnic groups (Profita & Bidder, 1988).…”
Section: Perfect Pitchmentioning
confidence: 99%
“…The “genetic hypothesis” states that AP is a genetically determined trait, and studies have pointed to genes associated with AP ( Theusch et al, 2009 ; Gregersen et al, 2013 ) and to a higher prevalence of high-performance AP among twins in comparison to non-twins ( Theusch and Gitschier, 2011 ; Bairnsfather et al, 2022a ). Finally, although initially disregarded, the “practice hypothesis” gained attention from the scientific community with recent studies showing that, with intensive training, some adults are capable of reaching an extraordinarily high and long-lasting precision at identifying pitches, comparable to musicians with “naturally” high AP ability ( Van Hedger et al, 2019 ; Wong et al, 2020a , 2020b ). Considered alone, however, these hypotheses fail to fully explain the characteristics variance observed in AP, thus reinforcing the notion that this phenomenon most likely arises from the interaction between genetic and environmental factors ( Zatorre, 2003 ; Bermudez and Zatorre, 2009a ; Szyfter and Witt, 2020 ).…”
Section: Introductionmentioning
confidence: 99%